2008
DOI: 10.1521/pedi.2008.22.3.233
|View full text |Cite
|
Sign up to set email alerts
|

How Do Personality Disorders Modify Suicide Risk?

Abstract: There is a lack of psychological autopsy studies assessing the influence of axis II disorders on other risk factors for suicide. Therefore, we investigated if the estimated suicide risk for axis I disorders and socio-demographic factors was modified by personality disorders. Psychiatric disorders were evaluated by a semi-structured interview including the Structured Clinical Interview for DSM-IV Axis I (SCID-I) and Personality Disorders (SCID-II) by psychological autopsy method in 163 completed suicides and by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 11 publications
4
37
0
Order By: Relevance
“…2,3 A high rate of acute in-patient admission is further associated with a high incidence of suicide among people with borderline personality disorder, estimated at 10%. 4 Partial hospitalisation over a 5-day week with a mentalisationbased treatment (MBT) approach to care has been shown to decrease this burden, reducing the duration of in-patient care among patients with borderline personality disorder, 5 in addition to a reduction in rates of self-harm and suicidality. 6,7 The provision of inexpensive open-access service user network (SUN) groups has also demonstrated effectiveness in reducing emergency department attendance among patients with personality disorder.…”
Section: Declaration Of Interest Nonementioning
confidence: 99%
“…2,3 A high rate of acute in-patient admission is further associated with a high incidence of suicide among people with borderline personality disorder, estimated at 10%. 4 Partial hospitalisation over a 5-day week with a mentalisationbased treatment (MBT) approach to care has been shown to decrease this burden, reducing the duration of in-patient care among patients with borderline personality disorder, 5 in addition to a reduction in rates of self-harm and suicidality. 6,7 The provision of inexpensive open-access service user network (SUN) groups has also demonstrated effectiveness in reducing emergency department attendance among patients with personality disorder.…”
Section: Declaration Of Interest Nonementioning
confidence: 99%
“…Comorbidity of Axis I and Axis II disorders is reported in 14 % (Vijayakumar and Rajkumar 1999 ) to 58 % of all suicide victims (Cheng et al 1997 ). Personality traits modify suicide risk differently depending on the underlying Axis I disorder (Schneider et al 2008 ). Having a depression and being substance dependent are themselves suicide risk factors.…”
Section: Comorbidity With Axis I Disordersmentioning
confidence: 99%
“…Having a depression and being substance dependent are themselves suicide risk factors. But when they are comorbid with a PD, the risk of suicide goes beyond the simple sum of relative risks (Schneider et al 2008 ). This may be particularly true for PDs in clusters B and C. For instance, the comorbidity of BPD and depression increased the number and seriousness of suicide attempts in a sample of inpatients (Soloff et al 2000 ).…”
Section: Comorbidity With Axis I Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Its association with an increased risk for suicide in our bivariate analysis (Table 3) suggests personality might play a role in averse-life-event-related "impulsive" suicide. Previously, a number of studies showed that the most attributing factors of personality disorders to suicidal behaviors were impulsivity, aggression, and hostility [37,[75][76][77][78][79][80][81][82][83][84][85][86] . Since about half of suicides in China were unplanned and impulsive, the relationship between personality traits/disorder and suicides is worthy of further exploration with larger sample size studies.…”
Section: Issn 2372-5923mentioning
confidence: 99%